Experience, Customer Satisfaction and Word of Mouth Intention on BCA Bank Customer Loyalty - Riyanta, Dylan Rachmat; Riorini, Sri Vandayuli; Arkaan Athooya Hadi (ProBisnis : Jurnal Manajemen, 2025)
This study aimed to examine the influence of customer experience, customer satisfaction, and word of mouth intention on customer loyalty in the banking sector, specifically among customers of Bank BCA. A quantitative method was used, and data were collected through a questionnaire distributed to 105 respondents using purposive sampling. Descriptive statistical analysis and hypothesis testing were conducted using SPSS and AMOS. The results showed that customer experience and word of mouth intention had a significant positive influence on customer loyalty, while customer satisfaction did not show a significant effect. This indicates that a positive customer experience such as responsive service and effective problem-solving can increase emotional bonds and loyalty. Furthermore, customers who intend to recommend the bank tend to be more loyal. However, satisfaction alone was not sufficient to foster loyalty without strong customer engagement or emotional connection.